کمالِ انسانیت : محبت و احترام ِ انسانیت سے متعلق خصائص کا سیرت النبی ﷺ کے تناظر میں ایک مطالعہThe Perfection of Humanity: A Study of the Traits Related to Love and Respect for Humanity in the Context of the Prophetic Sīra (Al-Qamar, 2022)
Man is a beautiful masterpiece of nature. By dint of his best fashion, having dignity and glory, blessed with reason and intellect, universe submitting to him, heir of knowledge and intuition and deserves vicegerency of Allah due to his service to mankind. Due to dignity and honor, sanctity of life, property and honor granted to him. Even the dignity if the blood of a believer is greater than the dignity of Kaaba. God created him, breathed into him His Spirit and gave him reason and logic. The secret of human dignity and superiority lies in the fact that he loves mankind and this love is also reciprocated by Allah. The key to success in all works of life is to respect and favor humankind. Security of human life, wealth and honor, proximity to God, salvation in the Afterlife, promotion of science and arts, nurturing and inculcating high moral values are not possible without establishing peace. It is indispensable to ensure non-violence, dignity of human life and love for all fellow human beings to make this world a center of love and peace.
Keywords: Accomplishment of Mankind; Dignity; Glory; Vicegerency; moral values